2009
DOI: 10.1001/jama.2009.96
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food Additives on Hyperphosphatemia Among Patients With End-stage Renal Disease

Abstract: NDIVIDUALS WITH MODERATE TOsevere renal disease have an impaired ability to excrete phosphorus. As a result, they tend to develop hyperphosphatemia, especially in settings of high phosphorus intake. Elevated serum phosphorus levels are independently associated with increased mortality and morbidity. For example, serum phosphorus levels greater than the 5.5-mg/dL level recommended by practice guidelines are independently associated with a 20% to 40% increase in mortality risk among patients with end-stage renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
225
1
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(243 citation statements)
references
References 40 publications
5
225
1
12
Order By: Relevance
“…Additional studies, including randomized, controlled trials, should examine whether restriction of nonprotein sources of P is safer and more effective. A recent randomized, controlled trial showed that P intake may be decreased by restricting intake of enhanced food with P-containing additives (37). Although it is possible that this dietary modification did not substantially reduce protein intake, the latter study did not present data on this question (37).…”
Section: Balancing Dietary Protein and P Intake In Ckdmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional studies, including randomized, controlled trials, should examine whether restriction of nonprotein sources of P is safer and more effective. A recent randomized, controlled trial showed that P intake may be decreased by restricting intake of enhanced food with P-containing additives (37). Although it is possible that this dietary modification did not substantially reduce protein intake, the latter study did not present data on this question (37).…”
Section: Balancing Dietary Protein and P Intake In Ckdmentioning
confidence: 99%
“…Because humans do not express the degrading enzyme phytase, the bioavailability of P from plant-derived food is relatively low, usually Ͻ50% (36). Hence, despite the "apparently" higher P content of some plants (see Table 1), the actual result may be a lower rate of intestinal P absorption per gram of plant protein than animalbased protein (37). When healthy humans are given the same amount of dietary P from either animal or plant foods, urinary P excretion is higher with the meat-based diet (38).…”
Section: P Intake From Plant Foods: the Role Of Phytatementioning
confidence: 99%
See 2 more Smart Citations
“…Restriction of dietary intake of phosphorus generally requires some reduction in the allowable protein intake (8) and restricted consumption of highly processed fast and convenience foods (16). However, imposing dietary phosphorus restriction can lead to obligatory reduction in dietary protein intake, which per se is associated with protein-energy wasting (PEW) (17) and increased mortality (8).…”
mentioning
confidence: 99%